Searching of Standard Comet Assay Parameters for Detecting Lymphocyte DNA Damages Using Fourteen Different Test Conditions - Kayaalti, Zeliha; Soylemez, Esma; Yalcin, Serap; Soylemezoglu, Tulin (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The alkaline single cell gel electrophoresis technique (SCGE), also known as the comet assay, is an evaluation method for estimating DNA damage and genotoxicity. This assay is used to measure DNA single-strand breaks, alkali-labile sites and DNA cross-linking in individual cells. Although the comet assay is a simple, sensitive, and rapid method to compare the results of previous studies, it is often difficult to interpret because of the variability among protocols. Standardisation and validation of the comet assay could provide invaluable information for the identification of hazardous substances and the risk assessment of environmental and occupational exposure. Further use of a standardised comet assay could include monitoring the effectiveness of medical treatment and the investigation of individual variation in response to DNA damage that may reflect genetic or environmental influences. In this study, the comet assay was evaluated for 4 parameters, including the tail moment (TM), tail intensity (TI), olive tail moment (OTM) and DNA tail (DNAt) length. 6 blood samples were collected from genetically unrelated healthy volunteers, and 7 different blood volume ranges (2.5 ml to 2.5 Âµl, diluted with PBS or RPMI) were tested for these parameters. The intraclass correlation coefficients (ICCs) were statistically significant among all 14 different test conditions (r=0.87, p<0.001 for TM; r=0.86, p<0.001 for TI; r=0.73, p<0.05 for OTM and r=0.87, p<0.001 for DNAt). In conclusion, the determination of DNA damage using the comet assay with small blood sample volumes can contribute worthwhile knowledge to future studies.